Perception of primary health professionals about Female Genital Mutilation: from healthcare to intercultural competence - Fàbregas Ma Jose; Moreno-Navarro Juana; Torán-Monserrat Pere; Kaplan-Marcusan Adriana; Muñoz-Ortiz Laura (BMC, 2009)
Abstract Background The practice of Female Genital Mutilation (FGM), a deeply-rooted tradition in 28 countries in Sub-Saharan Africa, carries important negative consequences for the health and quality of life of women and children. Migratory movements have brought this harmful traditional practice to our medical offices, with the subsequent conflicts related to how to approach this healthcare problem, involving not only a purely healthcare-related event but also questions of an ethical, cultural identity and human rights nature. Methods The aim of this study was to analyse the perceptions, degree of knowledge, attitudes and practices of the primary healthcare professionals in relation to FGM. A transversal, descriptive study was performed with a self-administered questionnaire to family physicians, paediatricians, nurses, midwives and gynaecologists. Trends towards changes in the two periods studied (2001 and 2004) were analysed. Results A total of 225 (80%) professionals answered the questionnaire in 2001 and 184 (62%) in 2004. Sixteen percent declared detection of some case in 2004, rising three-fold from the number reported in 2001. Eighteen percent stated that they had no interest in FGM. Less than 40% correctly identified the typology, while less than 30% knew the countries in which the practice is carried out and 82% normally attended patients from these countries. Conclusion Female genital mutilations are present in primary healthcare medical offices with paediatricians and gynaecologists having the closest contact with the problem. Preventive measures should be designed as should sensitization to promote stands against these practices.